(untitled) (Current Horticulture, 2024)
The effect of foliar application of organic liquids on growth, yield and quality of garlic (Allium sativum L.) cv. Yamuna Safed-3” was studied at Regional Horticultural Research Station, ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari, Gujarat during rabi season (2019-20). The experiment was laid out in randomized block design with three replications and nine treatments, viz. Panchagavya, novel plus, Jeevamrut and cow urine at each of 1% and 2% concentration and the control (no spray). The foliar application of Panchagavya @ 2 % (T2) gave significantly maximum plant height (55.05 and 60.61 cm at 75 and 90 DAP, respectively), whereas maximum number of leaves/plant (7.0 and 8.13 at 75 and 90 DAP, respectively) and minimum days to maturity (127.37 days) were also reported in novel plus @ 2 % (T4). The novel plus @ 2 % (T4) recorded significantly maximum fresh weight of bulbs (24.79 g), dry weight of bulbs (16.73 g), diameter of bulb (3.75 cm), number of cloves/ bulb (18.60), weight of clove (2.16 g), length of clove (3.48 cm) and yield of bulbs (3.97 kg/plot and 7.87 t/ha). The plants sprayed with novel plus @ 2 % (T4) recorded higher total soluble solids (16.87and 22.43 0Brix at 2 and 4 MAH, respectively), ascorbic acid content (20.30, 18.30 and 15.97 mg at 2, 4 and 6 MAH, respectively) with maximum storage life of 219.67 days at room temperature. However, maximum net income of ₹2,36,012/hawith a benefit: cost ratio of 3.00 was recorded in foliar spray of Novel plus @ 2 % (T4) as compared to rest of the treatments.